Future access enablers for ubiquitous and intelligent infrastructures : first International Conference, FABULOUS 2015, Ohrid, Republic of Macedonia, September 23-25, 2015, revised selected papers /: first International Conference, FABULOUS 2015, Ohrid, Republic of Macedonia, September 23-25, 2015, revised selected papers. (2015) - Unknown
No abstract available